Dissolution of Higher Education Foundation and Its Legal Consequences - A. Zulkarnain (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study focuses on the reasons for the dissolution of higher education foundations and their legal consequences. The research method used is Normative Juridical with a statutory approach, theories/concepts, cases related to the dissolution of higher education foundations. Then the data used is secondary data in the form of legal materials. The results of the study show that the reasons for dissolving or dissolving a foundation are 1)The period specified in the Articles of Association ends; 2) The goals of the Foundation set out in the Articles of Association have been achieved or not achieved; 3) Court decisions that have permanent legal force are based on the following reasons: The foundation violated public order and decency, was unable to pay its debts after being declared bankrupt, or the foundation's assets were insufficient to pay off its debts after the bankruptcy declaration was revoked(Article 62 UUY No.16 of 2001).However, according to Rudhi Prasetya, the Foundation can also be dissolved based on the decision of the Foundation Trustees Meeting which fulfills a 2/3 quorum and is approved by at least 2/3 of the votes present, this is not regulated in the Law or the Foundation's Articles of Association.The dissolution of the foundation must be followed by liquidation involving the builders, administrators, curators, prosecutors, creditors, and others who have an interest in the dissolving foundation.Foundations that are disbanded have legal consequences, namely that they cannot take legal action anymore, except for the Trustees and Management of the Foundation, they are obliged to follow the liquidation process until it is finished. The remaining assets resulting from the liquidation were handed over to other foundations that had the same activities as the disbanded foundation (Article 68 paragraph (1) UUY 2004). The dissolution of the foundation also has an impact on tertiary institutions as their activities/businesses, to be transferred to foundations of the same type or of the same nature and activities/business, in this case private higher education foundations (PTS).